Studies on existing neonatal calf managemental practices adopted by dairy farmers of Tarai region of Uttarakhand - Tewari, Himani; Kumar, Sanjay; SINGH, D V; Prasad, Shiv; Rath, Rajashree (Indian Journal of Animal Production and Management, 2018)
field survey was conducted to collect the information on neonatal management practices followed by the dairy animal owners in Tarai region of Uttarakhand. The results revealed that 100% of farmers clean mucous membrane of newborn calf immediately after birth. Around 74.38% allowed suckling within 15 minutes of birth and 23.12% between 30 minutes after birth. Majority of farmers 73.75% practiced feeding colostrum within half an hour of its birth and continuing upto the first five days. Practice of cutting and disinfection of navel cord after birth was uncommon (10%). Temporary identification method was common as compared to permanent type which were 87.50% and 12.50% respectively. Most of farmers feed their calves from two teats and 11.25% of farmers practice feeding of milk from all four teats. Dehorning was done by majority of the farmers (97.50%). Castration of male calves at 30-40, 40-50 and >50 days of age were practiced by 42.50, 27.50 and 23.75% of farmers respectively. Weaning of calves was done at 40-60 days of age by 83.12% of farmers. Key words: Colostrum, Dehorning, Neonates, Weaning Indian ranks first in the world in terms of milk production and contributes to about 14% of the total milk production of the world 3. Understanding the factors affecting farmers’ adoption of dairy technology is critical to success of development and implementation of policies and programmes in dairy industry development. Previous adoptionoriented research has examined the use and diffusion of